Validación del método analítico por cromatografía liquida de ultra alta resolución para la cuantificación de sulfametoxazol y trimetoprima en suspensión - Cruz Cancino, Arnol (2020)
The development and validation of the new analytical method by ultra-high-resolution liquid chromatography of sulfamethoxazole and trimethoprim in suspension was carried out in a national laboratory, carried out with the parameters specified in the current pharmacopoeia, such as instrumental precision, specificity, linearity of the system. , method linearity, accuracy and reproducibility. The resulting values for instrumental precision were RSD 0.32% and 0.35%, the specificity without interference for the analytes, system linearity with correlation coefficients of 0.9998 and 0.9999, coefficient of determination of 0.9995 and 0.9997, method linearity with correlation coefficients of 0.9991 and 0.9992, coefficient of determination of 0.9982 and 0.9984, accuracy with recovery values of 100.81% and 99.34%, precision with repeatability of 102.02% and 97.63% and with reproducibility 100.73 and 96.48% for sulfamethoxazole and trimethoprim respectively in each case, being within the requirements established by the American Pharmacopoeia 42. It is concluded that the development of the new analytical method by ultra high performance liquid chromatography for the quantification of sulfamethoxazole and trimethoprim complies with the validation according to the current American pharmacopoeia